Influence of calculation methods and model distribution of soil properties on the results of quantitative evaluation of slope stability - F. K. Bufeev; I. K. Fomenko (Известия высших учебных заведений: Геология и разведка)
The article gives the comparison of the slope stability calculation results using different types of soil properties distribution in the slope massive. Four models of soil properties distribution in the landslide hazardous slopes are considered: the way used in domestic engineering geological practice - soil properties parameter values are set within outlined geological items; the abroad practice way - soil properties normative values are set within selected lithological types; proposed to consider the new approaches - the values of soil properties are set discretely within the outlined geological items; values of the properties of soils are specified discretely in a massif. The analysis of the slope stability general assessment using different principles of soil properties distribution shows that they have influence on the sliding surface position and the coefficient of slope stability value. Therefore the slope stability problem correct solution must be performed with the substantiation of soil properties distribution model in the slope massive.